Monocyte‐Derived Interleukin‐1β As the Driver of S100A12‐Induced Sterile Inflammatory Activation of Human Coronary Artery Endothelial Cells: Implications for the Pathogenesis of Kawasaki Disease. Issue 5 (25th March 2019) - Armaroli, Giulia; Verweyen, Emely; Pretzer, Carolin; Kessel, Katharina; Hirono, Keiichi; Ichida, Fukiko; Okabe, Mako; Cabral, David A.; Foell, Dirk; Brown, Kelly L.; Kessel, Christoph
Abstract : Objective: Kawasaki disease (KD) is an acute vasculitis of childhood, predominantly affecting the coronary arteries. S100A12, a granulocyte‐derived agonist of both the receptor for advanced glycation end products (RAGE) and Toll‐like receptor 4 (TLR‐4), is strongly up‐regulated in KD. This study was undertaken to investigate the potential contributions of S100A12 to the pathogenesis of KD. Methods: Serum samples from patients with KD (n = 30) at different stages pre– and post–intravenous immunoglobulin (IVIG) treatment were analyzed for the expression of S100A12, cytokines, chemokines, and soluble markers of endothelial cell activation. Primary human coronary artery endothelial cells (HCAECs) were analyzed for responsiveness to direct stimulation with S100A12 or lipopolysaccharide (LPS), as assessed by real‐time quantitative reverse transcription–polymerase chain reaction analysis of cytokine and endothelial cell adhesion molecule messenger RNA expression. Alternatively, HCAECs were cultured in conditioned medium obtained from primary human monocytes that were stimulated with LPS or S100A12 in the absence or presence of IVIG or cytokine antagonists. Results: In the serum of patients with KD, pretreatment S100A12 levels were associated with soluble vascular cell adhesion molecule 1 titers in the course of IVIG therapy (rs = −0.6, P = 0.0003). Yet, HCAECs were not responsive to direct S100A12 stimulation, despite the presence of appropriate receptors (RAGE, TLR‐4). HCAECs did, however, respond to supernatants obtained from S100A12‐stimulated primary human monocytes, as evidenced by the gene expression of inflammatory cytokines and adhesion molecules. This response was strictly dependent on interleukin‐1β (IL‐1β) signaling ( P < 0.001). Conclusion: In its role as a highly expressed mediator of sterile inflammation in KD, S100A12 appears to activate HCAECs in an IL‐1β–dependent manner. These data provide new mechanistic insights into the contributions of S100A12 and IL‐1β to disease pathogenesis, and may therefore support current IL‐1–targeting studies in the treatment of patients with KD.